Estimación de aptitud combinatoria de líneas endogámicas y predicción de híbridos de maíz de alta calidad de proteína, Guatemala, 1988 - Soto León, Nery; Fuentes, Mario Roberto (Agronomía Mesoamericana, 2016)
Yellow grain hybrids of high quality protein can provide a comparative advantage because carotenes found in these materials are more easily taken up compared to normal hybrids. This advantage could provide added benefits within the poultry Industry. In this study, 91 possible crosses coming from 14 endogamic lines from the CIMMYT maize hybrid program were evaluated. The single crosses demonstrated superior adaptation notable in the coastal plain of Guatemala having grain yields approaching 7.0 Mg/ha along with excellent agronomic traits, decreased ear rot and uniform plant type. Superior hybrids demonstrated increased yields (average increase of I Mg/ha) versus the best natural check. Inbred parents 2, 1 and 6 demonstrated the highest values for general combinability and they were also amongst the best specific crosses. The yield levels, agronomic characteristics and the expression of stability in the modified endosperm of the single crosses that can be used as females to produce seed for double and three way crosses, suggests anew production alternative that could enhance the use of yellow grain hybrids of high protein quality in the tropical lowlands of Guatemala.